Computer Simulation Studies in Condensed-Matter Physics XVIII Proceedings of the Eighteenth Workshop, Athens, GA, USA, March 7-11, 2005 - Landau, David P.; Landau, David P.; Lewis, Steven P.; Lewis, Steven P.; Schüttler, Heinz-Bernd.; Schüttler, Heinz-Bernd. (Springer Proceedings in Physics,, 2006)
This volume represents a "status report" emanating from presentations made during the 18th Annual Workshop on Computer Simulations Studies in Condensed Matter Physics at the Center for Simulational Physics at the University of Georgia in March 2005. It provides a broad overview of the most recent advances in the field, spanning the range from statistical physics to soft condensed matter and biological systems. Results on nanostructures and materials are included as are several descriptions of advances in quantum simulations and quantum computing as well as.methodological advances.